Identificación de una zona de interés hídrica en el área de conservación y uso sustentable (ACUS) en la provincia de Bolívar - Larrea Berrones, Alexander Xavier (2025)
This study urgently focuses on identifying, prioritizing, and proposing conservation strategies for water sources within the Conservation and Sustainable Use Area (ACUS) of Bolívar Province, Ecuador. The research estimates average flows using hydrological modeling tools such as HEC-HMS, IDF curve analysis, and studies of the Piñanato, Suquibi, and Chimbo watersheds. It identifies priority water sources based on location, predominant use (human consumption), flow volumes, and cross-referencing with local parish data. Eight priority water concessions were identified, whose conservation is critical for ensuring water supply and environmental sustainability. Based on this prioritization, a management plan was proposed, including reforestation, land-use control, institutional strengthening, and environmental education. Key stakeholders in this effort include the NDT Project (CONDESAN), the Provincial Government of Bolívar, parish councils, community boards, and universities (UNACH, ESPOCH, and UEB). In this context, the findings underscore the importance of conserving areas with significant water recharge potential and implementing effective measures to protect water quality and availability. This study demonstrates how integrating technical tools, community participation, and interinstitutional collaboration is essential for the sustainable management of water resources in environmentally sensitive regions.